Development of Augmented Reality Code Application on 3D Animation in Learning Procedure at School - Banne Ima Gasong; Rufi'i Rufi'i; Hartono Hartono (Universitas Negeri Malang, 2021)
The use of AR (Augmented Reality) technology in the world of education continues to increase. Android as a booming trend is currently taking part in adopting AR technology. The ease and usefulness of Android-based AR technology can also be applied to the learning media development strategy. That spreads to the world community will also have an impact on students. Media Flyer Code as a marker on AR technology is applied to 3D Animation subjects. This study aims to determine the appropriateness of Augmented Reality Code Application especially the effectiveness, attractiveness, and efficiency of media. The product of this research and development is in the form of a Flyer Code product that will be used as a code and APK file. Each Flyer Code has one content that is run on the android application. In the augmented reality content contains 3D Animation Learning Procedure and questions contain evaluation material.